The Curing Characteristics, Thermal And Mechanical Properties Of Recycled Poly (Ethylene Terephthalate) And Hybrid Recycled Poly (Ethylene Terephthalate) Filled Natural Rubber Compounds - Hayeemasae, Nabil (2011)
The effects of recycled poly(ethylene terephthalate) (R-PET) power filled natural rubber compounds were investigated. The compounds were prepared on a laboratory size two-roll-mill at room temperature. Two different studies have been carried out; i) effect of R-PET loading up to 40 phr on the properties of natural rubber and epoxidized natural rubber, and ii) the hybridization of R-PET with commercial fillers on the properties of the rubber compounds.